Monster blood - Stine, R. L. (New York : Scholastic, 2008)
Evan begins to fear he has unleashed disaster when a dusty can of monster blood he bought at an old toy store starts to grow and acquire an appetite.
5.3
5-8
Keywords: Monsters -- Juvenile fiction; Horror stories; Monsters -- Fiction; Horror fiction; Monsters -- Fiction